Nonlinear dynamics of relativistic electron bunch in an undulator - Ognivenko, V.V. (Вопросы атомной науки и техники, 2001)
The dynamics of electron bunch motion in a helical undulator for the regime of self–amplification spontaneous undulator radiation is investigated theoretically using the method of self-consistent modeling the motion of electrons in the total field of their undulator radiation. The effects of bunch edge on start up processes are studied. The bunching of electrons within the radiation wavelength and within the full length of the beam is investigated. The efficiency of free–electron lasers using such beam is determined.